Menarquia temprana como factor de riesgo para asma bronquial. Hospital Belén de Trujillo-Perú - Romero Martínez, Glenn Miguel (2022)
Asthma is a chronic inflammatory disease of the respiratory tract, in whose pathogenesis various cells and inflammatory mediators are involved, conditioned in part by genetic factors. Early menarche is transient and isolated vaginal bleeding or cyclical bleeding in the absence of other signs of sexual development occurs in girls under 10 years of age. There is a detrimental role of the sex hormone in women with asthma before menstruation, as in girls with early menarche. This work tries to associate the age of menarche with subsequent respiratory health, specifically with asthma, its symptoms and bronchial reactivity. This study will be analytical, prospective, observational, cases and controls; It will be carried out in the Pediatric service of the Hospital Belén of Trujillo, with those women under 14 years of age, with a record of early menarche and bronchial asthma. For the statistical analysis of the data, the Fisher test will be used and to evaluate the risk factor, the Odds Ratio (OR) will be obtained. The confidence interval will be 95% and the statistical significance of p<0.05